Research on energy indexes of cogenerated plants with gas turbines and heat recuperator steam generators (2012)
The main objective of this paper is the experimental investigation of the energy indexes of a cogeneration plant with Gas Turbines (GT) and Heat Recuperator Steam Generators (HRSGs) while changing its operational load. The energy indicators were determined using the following International Standards and Codes: ASME PTC1, ASME PTC 22 and ASME PTC 4.4. The results of energy calculations indexes are in the form of curves. The mathematical equations of the curves corresponding to the real energy indexes are obtained applying multivariate regression. The main research results correspond to a process plant with nominal capacity of 4800 kW. The range of lower energy consumption values obtained for the HR of the turbine are around 13000 kJ/kW·h, while for the Heat Rate of the plant is 7000 kJ/kW·h. For these values of the Heat Rate (HR), the electrical output remains in the environment of 3500 kW. It was found that the thermal efficiency of HRSGs varies from 50 to 60% with very high values of sensible heat losses in flue gases due to the operation with high excess air and high temperatures of the gases at the outlet of HRSGs. The contributions of this research are used in operational management in order to reduce fuel consumption and environmental impact on the generation of electricity and heat cogeneration plant evaluated. The results of this research in the plant have been implemented to monitor the transaction on the basis of the variation in real-time energy indexes evaluated, besides the traditional control of the parameters only, which is more effective.